Technological Integration in Assessment Practices for Inclusive Education in Primary Schools - Iqbal, Muhammad Nadeem; Muhammad Shokat Zaman; Kishwar Sultana (JIE, 2025)
The study focused on investigating the technological integration in assessment practices for inclusive education in primary schools. A quantitative cross-sectional survey design was used to carry out the study. The sample of the study was 176 teachers teaching at the primary level in FGEIs (C/G) in the Multan region. Stratified random sampling was used to select the study's sample. The data was gathered using a questionnaire that was self-designed and validated. Frequency counts, percentages, one-sample t-tests, independent samples t-tests, and analysis of variance (ANOVA) were used to examine the collected data.The study revealed that teachers perceived positively the usage of technological tools in inclusive assessment. Moreover, teachers perceived that adaptive learning technologies can enhance inclusivity in assessment at the primary level significantly. Additionally, the study found significant differences in teachers' perceptions regarding the use of technological tools in inclusive assessment and the impact of adaptive learning technologies on inclusivity in assessment based on gender, i.e., male and female. However, there was no significant difference among teachers’ perceptions on the basis of professional qualification, academic qualifications, and teaching experience. The study recommended implementing the usage of technological tools in inclusive assessment and adaptive learning technologies to enhance inclusivity in assessment practices at the primary level to address the diverse needs of students. Moreover, teachers should be provided the opportunities of professional development regarding the use of adaptive learning technologies in assessment practices.